Low-Temperature Migration-Enhanced Epitaxial Growth of High-Quality (InAs)4(GaAs)3/Be-Doped InAlAs Quantum Wells for THz Applications - Linsheng Liu; Zhen Deng; Guipeng Liu; Chongtao Kong; Hao Du; Ruolin Chen; Jianfeng Yan; Le Qin; Shuxiang Song; Xinhui Zhang; Wenxin Wang (Crystals, 2024)
This investigation explores the structural and electronic properties of low-temperature-grown (InAs)4(GaAs)3/Be-doped InAlAs and InGaAs/Be-doped InAlAs multiple quantum wells (MQWs), utilizing migration-enhanced epitaxy (MEE) and conventional molecular beam epitaxy (MBE) growth mode. Through comprehensive characterization methods including transmission electron microscopy (TEM), Raman spectroscopy, atomic force microscopy (AFM), pump–probe transient reflectivity, and Hall effect measurements, the study reveals significant distinctions between the two types of MQWs. The (InAs)4(GaAs)3/Be-doped InAlAs MQWs grown via the MEE mode exhibit enhanced periodicity and interface quality over the InGaAs/Be-InAlAs MQWs grown through the conventional molecule beam epitaxy (MBE) mode, as evidenced by TEM. The AFM results indicate lower surface roughness for the (InAs)4(GaAs)3/Be-doped InAlAs MQWs by using the MEE mode. Raman spectroscopy reveals weaker disorder-activated modes in the (InAs)4(GaAs)3/Be-doped InAlAs MQWs by using the MEE mode. This originates from utilizing the (InAs)4(GaAs)3 short period superlattices rather than InGaAs, which suppresses the arbitrary distribution of Ga and In atoms during the InGaAs growth. Furthermore, pump–probe transient reflectivity measurements show shorter carrier lifetimes in the (InAs)4(GaAs)3/Be-doped InAlAs MQWs, attributed to a higher density of antisite defects. It is noteworthy that room temperature Hall measurements imply that the mobility of (InAs)4(GaAs)3/Be-doped InAlAs MQWs grown at a low temperature of 250 °C via the MEE mode is superior to that of InGaAs/Be-doped InAlAs MQWs grown in the conventional MBE growth mode, reaching 2230 cm2/V.s. The reason for the higher mobility of (InAs)4(GaAs)3/Be-doped InAlAs MQWs is that this short-period superlattice structure can effectively suppress alloy scattering caused by the arbitrary distribution of In and Ga atoms during the growth process of the InGaAs ternary alloy. These results exhibit the promise of the MEE growth approach for growing high-performance MQWs for advanced optoelectronic applications, notably for high-speed optoelectronic devices like THz photoconductive antennas.